Enhancing fiber-matrix interface in carbon fiber/poly ether ether ketone (CF/PEEK) composites by carbon nanotube reinforcement of crystalline PEEK sizing - Wang, Shengdao; Wang, Tianjiao; Zhang, Shuwen; Dong, Zhongxin; Chevali, Venkata S.; Yang, Yanchao; Wang, Guibin; Wang, Hao (Composites. Part B, Engineering, 2023)
Crystalline poly ether ether ketone (PEEK) is an emergent effective sizing agent for carbon fiber (CF) for use in CF/PEEK composites. Soluble PEEK with the ability to recover crystallinity via simple acidification was synthesized and grafted on carbon nanotube for the first time to enhance the effectiveness and thermomechanical integrity of the based sizing, to achieve a higher level of chemical resistance and interfacial enhancement. CNT-filled, acidified-CNT-filled, and PEEK-grafted-CNT-filled sizing compounds were synthesized and coated on to CF. Proton nuclear magnetic resonance (1H NMR) and Fourier-transform infrared (FTIR) spectroscopy were used to analyze the products of chemical synthesis, whereas X-ray photoelectron spectroscopy (XPS) was used to assess the grafting reaction. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used to assess the morphology of the unsized and sized CF, and a microbond test was used to evaluate the interfacial shear strength (IFSS) of the sizing. As a result, the CF/PEEK composites achieved the highest ever reported IFSS, with values of 101.4 MPa and 103.4 MPa in the acidified-CNT and PEEK-grafted-CNT samples, respectively. It is noted that the PEEK-grafted-CNT sample also exhibited greater solvent resistance due to closer interfacial distance, and an IFSS retention rate of 80%–90% in various polar and non-polar solvents. The successful application of nano-reinforcement in a CF interfacial sizing and the development of the PEEK grafting on CNT possesses an expanded application potential for CF/PEEK composites. [Display omitted]